FDMA-based kite flap reconstruction for post-burn first web space contractures: A retrospective study: Treatment of first web space burn contractures - Melikoglu, Cenk (Journal of Surgery and Medicine, 2026)
Background/Aim: Post-burn first web space contractures significantly impair thumb abduction and overall hand function. This study aimed to evaluate the short- to mid-term clinical outcomes of a first dorsal metacarpal artery (FDMA)–based kite flap following complete release of post-burn first web space contractures. Methods: This retrospective case series included five patients with post-burn first web space contracture. In all cases, complete release of the contracture was performed, followed by reconstruction of the resulting defect using an FDMA-based kite flap. In one patient, a concomitant fifth-finger flexion contracture was corrected with a cross-finger flap during the same session. The primary outcome measure was first web space opening, assessed preoperatively and postoperatively using a goniometer in a standardized clinical position. Results: The mean preoperative first web space opening was 70.0 (3.5), which increased to 90.0 (0.0) postoperatively, corresponding to a mean improvement of 20.0 (3.5). Follow-up ranged from 5 to 7 months. In all patients, the achieved web space opening was preserved throughout follow-up, and no residual or recurrent contracture was observed. Conclusion: Reconstruction of post-burn first web space contractures using an FDMA-based kite flap after adequate release provides reliable restoration and maintenance of web space opening in the short to mid-term. This technique represents a stable and functional reconstructive option in selected patients when a true soft tissue defect is present after contracture release.